Metabolically Healthy Obesity - Catherine M. Phillips (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Accumulating evidence suggests that not all obese subjects are at increased cardiometabolic risk and that the "metabolically healthy obese" phenotype may exist in the absence of metabolic abnormalities. Limited data regards the determinants of metabolically healthy obesity exist, particularly in relation to genetics, dietary and lifestyle behaviours. In light of the current obesity epidemic, it is clear that current "one size fits all" approaches to tackle obesity are largely unsuccessful. Whether dietary, lifestyle and/or therapeutic interventions, based on stratification of obese individuals according to their metabolic health phenotype, are more effective remains to be seen, with limited and conflicting data available. This book includes original research articles and reviews of the scientific literature that contribute to our understanding of the role of clinical, biological, genetic, and environmental factors in metabolically healthy and unhealthy obesity.